A comprehensive evolutionary scenario for the origin and neofunctionalization of the Drosophila speciation gene Odysseus (OdsH) - Boas Nunes, William Vilas [UNESP]; Oliveira, Daniel Siqueira [UNESP]; de Rezende Dias, Guilherme; Carvalho, Antonio Bernardo; Caruso, Ícaro Putinhon [UNESP]; Biselli, Joice Matos [UNESP]; Guegen, Nathalie; Akkouche, Abdou; Burlet, Nelly; Vieira, Cristina; Carareto, Claudia M.A. [UNESP] (Oxford University Press (OUP), 2024)
Odysseus (OdsH) was the first speciation gene described in Drosophila related to hybrid sterility in offspring of mating between Drosophila mauritiana and Drosophila simulans. Its origin is attributed to the duplication of the gene unc-4 in the subgenus Sophophora. By using a much larger sample of Drosophilidae species, we showed that contrary to what has been previously proposed, OdsH origin occurred 62 MYA. Evolutionary rates, expression, and transcription factor-binding sites of OdsH evidence that it may have rapidly experienced neofunctionalization in male sexual functions. Furthermore, the analysis of the OdsH peptide allowed the identification of mutations of D. mauritiana that could result in incompatibility in hybrids. In order to find if OdsH could be related to hybrid sterility, beyond Sophophora, we explored the expression of OdsH in Drosophila arizonae and Drosophila mojavensis, a pair of sister species with incomplete reproductive isolation. Our data indicated that OdsH expression is not atypical in their male-sterile hybrids. In conclusion, we have proposed that the origin of OdsH occurred earlier than previously proposed, followed by neofunctionalization. Our results also suggested that its role as a speciation gene might be restricted to D. mauritiana and D. simulans.
Keywords: Drosophilidae; gene duplication; homeodomain; OdsH expression; transcription factor; unc-4